Where Next for Historic Landscape Characterisation (HLC)?. (2nd July 2020) - Herring, Peter; Dabaut, Niels; Last, Jonathan
ABSTRACT: This paper introduces a special issue on Historic Landscape Characterisation. It places in its wider context the development of HLC from the 1990s to the present, beginning with unpicking the implications for understanding and practice inherent in the meanings of the three constituent terms, historic (or historical), landscape and characterisation. The discussion includes consideration of society's changing approaches to understanding, presenting and managing landscape and place, and especially their comprehensively historical aspects. It also introduces the main trends that seem likely to influence the continued development of HLC and its application by decision makers.